Diet and esophageal disease. (29th September 2014) - Dawsey, Sanford M.; Fagundes, Renato B.; Jacobson, Brian C.; Kresty, Laura A.; Mallery, Susan R.; Paski, Shirley; van den Brandt, Piet A.
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on macronutrients, dietary patterns, and risk of adenocarcinoma in Barrett's esophagus; micronutrients, trace elements, and risk of Barrett's esophagus and esophageal adenocarcinoma; the role of mate consumption in the development of squamous cell carcinoma; the relationship between energy excess and development of esophageal adenocarcinoma; and the nutritional management of the esophageal cancer patient.